Bullies, victims and bully-victims: do they have a different health profile? - Seixas, Sónia Raquel Pereira Malta Marruaz (2021)
Bullying affects an important number of students in school today. A substantial body of international research supports this concern relating bully/victim problems and health. Following the concept of health defended by the World Health Organization (WHO), that focus on physical, mental and social aspects of subjects, in this paper we will present some results of a research concerning the relation between involvement in bullying and some health behaviours. Data was collected from a random sample, using the Health Behaviours in School-aged Children (HBSC) used by the WHO to assess, among others, physical symptoms, psychological symptoms and substance use, the Harter Self-Perception Profile for Adolescents, a Peer Nomination Inventory and a Sociometric Questionnaire. A total of 581 portuguese adolescents aged 12 to 17 years, who attended several middle public schools in the region of Lisbon. The students were defined as bullies, victims, bully-victims and not involved on the basis of the Peer nomination Inventory. Results show a connection between these four groups and some health behaviours, providing a distinctive profile for each one.